Russian manufacturing industry development in the context of import substitution - I. V. Davletshina (Вестник университета, 2024)
The relevance of the study is emphasized by the urgent need caused by the sanctions and geopolitical tensions, which manifested itself in disruptions in the foreign materials and consumer goods inflow to Russia.   This in turn affected the operation of the country’s vast manufacturing sector. Such a scenario requires innovative conceptual paradigms development for managing the industrial sector in the forced import substitution era. This article attempts to identify and critically evaluate both existing and emerging strategic directions required to upgrade the nation’s industrial machinery to ensure its operational efficiency in the present circumstances. A scholarly effort con sisting of a thorough analysis and expert papers synthesis relevant to this issue has formed the basis of the study. The ways of solving the problems facing the Russian manufacturing industry in the conditions of forced adaptation and modernization have been traced and identified. The socio-economic vector occupies a central place in the formulated resolution, proclaiming the harmonious unification of efforts to diversify production as a potential lever to stimulate inter-sectoral industrial growth. The author has not only identified various areas ripe for strategic transformation, but also emphasized the critical turn towards a socio-economic trajectory that seeks to utilize all available factors. Collective organization of diversified industrial activities can indeed serve as a catalyst to break the current industrial impasse.